THE EFFECT OF DRYING TIME BY USING GREEN HOUSE EFFECT ON THE QUALITY OF SKIPJACK (Katsuwonus pelamis) KATSOUBUSHI - Osemaking, Maria Fansiska; Leksono, Tjipto; Sukirnomus, Sukirnomus (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The aim of this study was to determine the effect of varied drying time in the greenhouse effect chamber on the quality of skipjack (Katsuwonus pelamis) katsoubushi. The method used was the experimental which was designed for Completely Randomized Design (CRD). The treatment conducted was drying the smoke flavoured skipjack for different drying time (48, 60, and 84 hours) in the solar drying chamber, and then fermenting them for producing katsuobushi.  The quality and characteristics of katsoubushi produced were evaluated for their proximate analyzes (moisture content, ash content, and phenol content) and microbiological tests (TPC and fungal identification). The results showed that the best quality of skipjack katsoubushi was produced by drying the fish for 84 hours. The organopeltic evaluation showed that the value of appearance was 7.8, odor 8.2, taste 7.4, and texture 8.5. Approximately, the content of moisture was 15.54 %, ash was 6.08 %, total phenolic compound was 1.29 ppm and Total number of bacteria (TPC) was 2.2 X 104 cfu/g. The fungi grown in all produced sample was Aspergillus sp. Key words :Drying time,Katsoubushi,Skipjack,